2020
DOI: 10.1186/s12879-020-05701-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tocilizumab in COVID-19 patients: a cohort study

Abstract: Background Due to the lack of proven therapies, we evaluated the effects of early administration of tocilizumab for COVID-19. By inhibition of the IL-6 receptor, tocilizumab may help to mitigate the hyperinflammatory response associated with progressive respiratory failure from SARS-CoV-2. Methods A retrospective, observational study was conducted on hospitalized adults who received intravenous tocilizumab for COVID-19 between March 23, 2020 and Ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
3
30
1
Order By: Relevance
“…There was no significant difference in multivariable logistic regression analysis between the two groups regarding CRE detection (p = 0.34). Our results contradict those of a prospective observational study conducted to assess the predictors of superinfections in patients with COVID-19 [ 32 ]. This study showed that CRE caused 52 episodes of MDR infections and reported a significant difference (p = 0.001) between IL6 users and non-users in terms of superinfection rate.…”
Section: Discussioncontrasting
confidence: 99%
“…There was no significant difference in multivariable logistic regression analysis between the two groups regarding CRE detection (p = 0.34). Our results contradict those of a prospective observational study conducted to assess the predictors of superinfections in patients with COVID-19 [ 32 ]. This study showed that CRE caused 52 episodes of MDR infections and reported a significant difference (p = 0.001) between IL6 users and non-users in terms of superinfection rate.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 204 records were excluded after screening the titles/abstracts because they did not match our inclusion and exclusion criteria. After evaluating 30 full-texts for eligibility, 5 full-text articles were excluded because they do not have the outcome of interest (severe COVID-19, ICU admission, the need for mechanical ventilation, and mortality), 3 full-text articles were excluded because they do not have the control/comparison group, 1 full-text article were excluded because the articles were not in English, and finally, 21 studies 15 , 16 , 17 , 18 , 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 with a total of 54,276 COVID-19 patients and 4,640 patients with OSA were included in the meta-analysis ( Figure 1 ). Of a total of 21 included studies, 19 were retrospective cohort, 1 study was a prospective cohort, while the remaining 1 study was a case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we might postulate that low dose tocilizumab (<8 mg/kg) may not be sufficient to provide optimal effect in patients with COVID-19 associated CRS. In a recent retrospective study, lower doses of tocilizumab administration (400 mg for 30-100 kg and 600 mg over 100 kg) was related to a rebound of CRP levels, suggesting the need for higher and/or repeated doses of tocilizumab [34].…”
Section: Discussionmentioning
confidence: 99%